Comparative visibility of four spoken languages - HJ, Oyer; R, Richard; R, Rajaguru; YP``Kapur (Journal of All India Institute of Speech and Hearing, 1972)
Casual observation of persons speaking different languages reveals that some languages are more highly visible than others. This observation is not only of academic interest to the linguist but also of interest to the rehabilitative audiologist who wishes to add to his store of information concerning the effects of "code" upon the lipreadability of certain languages. The authors are quite cognizant of the fact, however, that there is variability within languages vis-a-vis visibility, as a function of individual speaker differences, and also as a function of the language units spoken. Through the use of an appropriate experimental design and careful administration of an experiment, it is possible to obtain data concerning visibility of languages that lend themselves to treatment which provide a base for making reasoned generalizations about the relative visibility of languages.